2012
DOI: 10.1242/jcs.097667
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin Nuclear-Cytoplasmic Shuttling Affects Cofilin-Actin Rod Formation During Stress

Abstract: SummaryCofilin protein is involved in regulating the actin cytoskeleton during typical steady state conditions, as well as during cell stress conditions where cofilin saturates F-actin, forming cofilin-actin rods. Cofilin can enter the nucleus through an active nuclear localization signal (NLS), accumulating in nuclear actin rods during stress. Here, we characterize the active nuclear export of cofilin through a leptomycin-B-sensitive, CRM1-dependent, nuclear export signal (NES). We also redefine the NLS of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 52 publications
2
81
1
Order By: Relevance
“…One of the mechanisms that contribute to the maintenance of nuclear actin levels is mediated by an interaction between cofilin and importin-9 (Dopie et al, 2012) (see poster). Actin does not have a classic NLS, whereas cofilins have a bipartite NLS that allows for their efficient shuttling into the nucleus (Munsie et al, 2012). Importin-9 interacts with actin in a cofilin-dependent manner (likely to be mediated through the cofilin NLS), and this interaction is crucial for the nuclear transport of actin, which in turn influences the level of transcription (see also below) (Dopie et al, 2012).…”
Section: Nuclear Actin Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the mechanisms that contribute to the maintenance of nuclear actin levels is mediated by an interaction between cofilin and importin-9 (Dopie et al, 2012) (see poster). Actin does not have a classic NLS, whereas cofilins have a bipartite NLS that allows for their efficient shuttling into the nucleus (Munsie et al, 2012). Importin-9 interacts with actin in a cofilin-dependent manner (likely to be mediated through the cofilin NLS), and this interaction is crucial for the nuclear transport of actin, which in turn influences the level of transcription (see also below) (Dopie et al, 2012).…”
Section: Nuclear Actin Transportmentioning
confidence: 99%
“…As well as an NLS, cofilin also has a nuclear export signal (NES), which mediates its transport out of the nucleus (Munsie et al, 2012). Under stress conditions, such as heat shock, osmotic stress or ATP depletion, cofilin accumulates in the nucleus where it excessively binds to, and saturates, actin filaments, resulting in the formation of cofilin-actin 'rods'.…”
Section: Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…538 We also found that CFL2 (cofilin, muscle isoform) was up-modulated in response to 539 PSS. Cofilin is an isoform of the actin depolymeration factor family involved in 540 regulating the actin cytoskeleton and in other multiple facets of cellular biology [59]. It 541 has the ability to bind G-and F-actin in a 1:1 ratio of cofilin to actin and is the major 542 component of intranuclear and cytoplasmic actin rods.…”
Section: Tof/tof Ms (Supplementarymentioning
confidence: 99%
“…Together, cofilin and Htt bind nuclear actin and form many small cofilin-actin rods [114,115]. This process temporarily halts nuclear actin treadmilling, resulting in decreased ATP consumption and increased availability of cellular ATP that can subsequently contribute to additional cellular stress response mechanisms to aid in recovery from acute stress events [114,115].…”
Section: Wild Type Huntington Functionsmentioning
confidence: 99%